2013
DOI: 10.1007/7081_2013_100
|View full text |Cite
|
Sign up to set email alerts
|

The McMurry Reaction in Porphyrinoid Chemistry

Kevin M. Smith

Abstract: The McMurry reaction, first reported in 1974, is an organometallic coupling reaction of aldehydes and ketones, to give alkenes, that relies upon the use of low-valent titanium; the reactive titanium species is obtained from titanium (III) or titanium(IV) chloride and an in situ reducing agent. The first application of the McMurry reaction to polypyrrole chemistry took place in 1986 with the first synthesis of the (2,0,2,0)-porphyrin isomer, porphycene. Since then, numerous macrocyclization reactions of polypyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Insertion of the formyl group into porphyrins is a primary functionalization of the tetrapyrrole ring, opening opportunities for further transformations including, but not limited to, Wittig [12][13][14], Grignard [14][15][16], McMurry [17], cycloaddition [18], Knoevenagel [19] reactions, and Schiff bases preparation [20]. Ponomarev made a considerable contribution to the chemistry of formylporphyrins and published a corresponding review about 30 years ago, summarizing works reported up to that date [5].…”
Section: Meso-formylporphyrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insertion of the formyl group into porphyrins is a primary functionalization of the tetrapyrrole ring, opening opportunities for further transformations including, but not limited to, Wittig [12][13][14], Grignard [14][15][16], McMurry [17], cycloaddition [18], Knoevenagel [19] reactions, and Schiff bases preparation [20]. Ponomarev made a considerable contribution to the chemistry of formylporphyrins and published a corresponding review about 30 years ago, summarizing works reported up to that date [5].…”
Section: Meso-formylporphyrinsmentioning
confidence: 99%
“…Transformation of the formylporphyrins into dimers bonded with an ethene bridge can be performed using low-valent titanium, which is called the McMurry reaction [17] Cu(II) and Ni(II) complexes of OEP-CHO were dimerized under the action of TiCl3 and Zn/Cu to form the corresponding complexes of dimers linked with the ethylene bridge in the form of a mixture of cis and trans isomers (Scheme 26) [69]. Transformation of the formylporphyrins into dimers bonded with an ethene bridge can be performed using low-valent titanium, which is called the McMurry reaction [17]. Cu(II) and Ni(II) complexes of OEP-CHO were dimerized under the action of TiCl 3 and Zn/Cu to form the corresponding complexes of dimers linked with the ethylene bridge in the form of a mixture of cis and trans isomers (Scheme 26) [69].…”
Section: Reactions Of Meso-formylporphyrins With Organometallic Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of the parent porphycene 2a is straightforward (four steps from pyrrole); , however, the synthesis of substituted derivatives requires more elaborate synthetic schemes . In general, these syntheses rely on the use of three key reactions: Ullmann reaction to provide the 2,2′-bipyrrole moiety and Vilsmeier–Haack formylation and McMurry coupling to cause the cyclization that leads to a macrocycle, which is oxidized, often in situ, to furnish the corresponding aromatic porphycene (Scheme ).…”
Section: Porphycenesmentioning
confidence: 99%
“…Once the required bipyrrolic aldehydes are in hand, the next step is formation of the macrocyclic framework by reductive coupling via the McMurry reaction (Scheme ). This reaction is arguably the most complex step in the synthesis of porphycenes in terms of having a practical procedure.…”
Section: Porphycenesmentioning
confidence: 99%